Persepsi Siswa Terhadap Kompetensi Kepribadian Guru Di Sekolah Menengah Kejuruan (SMK) Negeri 1 Solok - Dilweni Permata Wahyu; Ahmad Sabandi; Nelfia Adi; Lusi Susanti (Universitas Negeri Padang, 2021)
The purpose of this study was made to see and get information about how capable students' perceptions of teacher personality competence are in carrying out their duties. There are five questions to be answered in this study, namely 1) How do students 'perceptions of the personality of the noble character possessed by the teacher in carrying out their duties at Vocational High School (SMK) Negeri 1 Solok, 2) How do students' perceptions of a personality that is steady and stable teachers have in carrying out their duties in Vocational High School (SMK) Negeri 1 Solok, 3) How do students' perceptions of the adult personality possessed by the teacher in carrying out their duties at Vocational High School (SMK) Negeri 1 Solok, 4) What is the student's perspective about the wise and wise personality possessed by teachers in carrying out their duties at Vocational High School (SMK) Negeri 1 Solok, 5) How do students' perceptions of the authoritative personality possessed by teachers in carrying out their duties at Vocational High School (SMK) Negeri 1 Solok. This type of research is quantitative descriptive with the population in this study are all students of class XI and XII at SMK Negeri 1 Solok with 955 students and a sample of 91 people. Sampling was determined using the Slovin formula and taken using simple random sampling technique. The research instrument used was a questionnaire with a Likert scale model, amounting to 30 statements. The data collected is then processed and the average score (mean) and the respondent's level of achievement (TCR) are sought. The results of data processing show that the teacher's personality competence seen from the indicators of noble character gets an average score of 3.83 with a respondent's achievement level (TCR) of 76.6%, a steady and stable personality gets an average score of 3.65, the respondent's level of achievement ( TCR) 73%, adult personalities get an average score of 3.59 with the respondent's achievement level (TCR) 71.8%, wise and wise personalities get an average score of 3.53 with a respondent's achievement level (TCR) of 70, 6%, and an authoritative personality got an average score of 3.63 with the respondent's achievement level (TCR) of 72.6%. Overall students' perceptions of teacher personality competence in Vocational High School (SMK) Negeri 1 Solok obtained an average score of 3.64 with a respondent's achievement level (TCR) of 72.8%..